(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The psychological relationship between teachers and students has long been recognized as a crucial factor in effective teaching and learning. A positive and supportive teacher-student relationship fosters an environment that promotes academic engagement, emotional well-being, and personal growth. This scientific article explores the significance of the teacher-student relationship in the context of personal development within the science of pedagogy. It delves into the essential elements that contribute to a healthy psychological relationship, highlights the benefits it brings to both teachers and students, and presents strategies for improving and nurturing this vital connection. By recognizing the significance of the teacher-student relationship and implementing techniques to enhance it, educators can foster an optimal learning environment that supports students’ holistic development.